EXAMINING THE RELATIONSHIP BETWEEN STUDENTS’ CREATION OF SPECIFIC DIGITAL PRODUCTS AND THEIR TECHNOLOGY ASSESSMENT SCORES - Zhang, Mingyuan; Sutter, Tiffany (International Journal of Research -GRANTHAALAYAH, 2020)
This study presented a secondary analysis of the National Assessment of Educational Progress (NAEP) dataset. The paper examined the impact of eighth grade students’ specific digital product creation on their Technology & Engineering Literacy ICT scores. In order to gain a better understanding of the impact of computer use technology achievement of eighth-grade students, this study used a quantitative descriptive research design to analyze secondary data extracted from the 2018 NAEP data set. The findings include (1) using computers to create, edit, or organize digital media both for school work and activities beyond school increased overall ICT scores. (2) The average score of students who used computers to create presentations in school increased while those who did this activity after school time saw a decrease in scores. (3) Students who reported that they create spreadsheets mostly saw a decrease in their average ICT score no matter the frequency or purpose for the activity. These findings may indicate that there is an ideal frequency for digital product creation in school, but that these types of activities may not be indicative of real-world use which is how students are assessed.